Diabetes as the risk of cancer: a literature review - Tedjamartono, Theodore Dharma (International Journal of Research in Medical Sciences, 2021)
Cancer is a non-communicable disease with high mortality and morbidity rates. Data recorded by GLOBOCAN in 2018 shows the number of cancer patients is reached 18 million people with a death rate of 9 million people and predicted to increase every year. Diabetes is known to affect morbidity and mortality in cancer patients through increasing cancer cell proliferation and the risk of metastasis. This literature study not only explains the epidemiology, but also the mechanisms underlying the association of diabetes to cancer in general. Literature search was done using four search engines from PubMed, ProQuest, Science Direct and Google Scholar in the last 5 year, but relevant older articles were included. Cancer occurs due to the carcinogenesis process. This process is complex, where normal cells do not immediately mutate and become cancer cells but through several stages. The possible mechanisms underlying carcinogenesis in diabetic patients are hyperglycaemia, hyperinsulinemia, chronic inflammation, genetic variation, obesity, and hyperlactatemia. Examination of sugar levels in cancer patients, as well as cancer screening in patients with diabetes need to be done to detect early events and reduce morbidity and mortality.